How RDA is essential in the reconciliation and conversion processes for quality Linked Data - Tiziana Possemato (JLIS.it, 2018)
RDA (Resource Description and Access), was initially released in 2010 and, as it is particularly appropriate for use by libraries, archives and museums, it replaces the Anglo-American Cataloguing Rules, Second Edition (AACR2). It provides a new structure for the organization of bibliographic data based on the Functional Requirements for Bibliographic Records (FRBR), with more emphasis on identifiers and relationships than on descriptions. In November 2016 the RDA Steering Committee announced steps toward progressive adoption of the IFLA Library Reference Model (LRM). RDA supports the Linked Data environment also through the representation of RDA entities, elements, relationship designators and vocabulary encoding schemas in Resource Description Framework (RDF, the syntax of the semantic web) in the RDA Registry. The paper is concerned with the application of the RDA standard within the field of Linked Data and how it may be used to improve the quality of the data produced to reach the advantages that the semantic web can bring to the cultural heritage sector. More specifically it will look at a series of Share Linked Open Data (SHARE-LOD) projects.